2021
DOI: 10.1111/liv.14836
|View full text |Cite
|
Sign up to set email alerts
|

Is elimination of hepatitis C virus realistic by 2030: Eastern Europe

Abstract: The WHO elimination goals (diagnosis of 90% of the cases of hepatitis C virus (HCV), treatment coverage in 80% and a 65% reduction in deaths from HCV) are set to be reached by 2030. Although these elimination programmes are extremely important in the Eastern European countries (Russia, Ukraine, Belarus and Moldova) with a high prevalence of HCV, limited economic resources prevent their development and implementation. Regardless of the decrease in the incidence HCV in all Eastern European countries, low diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…A recent survey of primary care professionals indicated that most HCV testing among existing migrant patients was done opportunistically rather than through systematic identification of high-risk patients, with only 17% of respondents stating that they offered universal opt-out HCV testing to newly registering migrant patients [ 51 ]. Specific barriers that migrants may face in accessing testing and subsequent linkage to care include language [ 52 ] (with a fifth of pregnant women screening positive for hepatitis B in England in 2014 having a less than basic level of English) [ 53 ], uncertainties around migrants’ entitlement to healthcare (which also exist among healthcare professionals) [ 51 ], and possible intersectional risk, particularly relating to IDU among migrants from Eastern Europe [ 54 , 55 ]. Furthermore, the lack of identifiable risk factors for some women may fail to identify some infected women, as was seen more than 20 years ago with selective antenatal screening for HIV in the UK [ 56 ], resulting in missed opportunities for postpartum treatment or follow-up of the HCV-exposed child.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of primary care professionals indicated that most HCV testing among existing migrant patients was done opportunistically rather than through systematic identification of high-risk patients, with only 17% of respondents stating that they offered universal opt-out HCV testing to newly registering migrant patients [ 51 ]. Specific barriers that migrants may face in accessing testing and subsequent linkage to care include language [ 52 ] (with a fifth of pregnant women screening positive for hepatitis B in England in 2014 having a less than basic level of English) [ 53 ], uncertainties around migrants’ entitlement to healthcare (which also exist among healthcare professionals) [ 51 ], and possible intersectional risk, particularly relating to IDU among migrants from Eastern Europe [ 54 , 55 ]. Furthermore, the lack of identifiable risk factors for some women may fail to identify some infected women, as was seen more than 20 years ago with selective antenatal screening for HIV in the UK [ 56 ], resulting in missed opportunities for postpartum treatment or follow-up of the HCV-exposed child.…”
Section: Discussionmentioning
confidence: 99%
“…About 71 million people worldwide are infected with hepatitis C [1]. The prevalence in Eastern European countries is 2-3% [2][3][4]. Patients with advanced liver disease or fibrosis should be treated promptly [5].…”
Section: Introductionmentioning
confidence: 99%